2003
DOI: 10.1086/368248
|View full text |Cite
|
Sign up to set email alerts
|

Iron Is Not Depleted in High-Ionization Nuclear Emission-Line Regions of Active Galactic Nuclei

Abstract: To examine whether or not high-ionization nuclear emission-line regions (HINERs) in narrow-line regions of active galactic nuclei are dusty, we focus on two high-ionization forbidden emission lines, [Fe vii consistent with the dust-free models, while it cannot easily be explained by the dusty models. This suggests that iron is not depleted in HINERs, which implies that the HINERs are not dusty. This result is consistent with the idea that the HINERs are located closer than the dust-sublimation radius (i.e., th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 73 publications
(103 reference statements)
1
17
0
Order By: Relevance
“…These results suggest that the Civλ1549, Heiiλ1640 and Ciii]λ1909 emitting regions in NLRs are dust-free. This is consistent with previous works in that gas clouds in the high-ionization part of NLRs are dust-free (e.g., Marconi et al 1994;Ferguson et al 1997;Nagao et al 2003). We verified that the effects of changing the grain composition (see Ferland 1997 for details) are less than 30% for the line flux ratios.…”
Section: Dust Grainssupporting
confidence: 93%
“…These results suggest that the Civλ1549, Heiiλ1640 and Ciii]λ1909 emitting regions in NLRs are dust-free. This is consistent with previous works in that gas clouds in the high-ionization part of NLRs are dust-free (e.g., Marconi et al 1994;Ferguson et al 1997;Nagao et al 2003). We verified that the effects of changing the grain composition (see Ferland 1997 for details) are less than 30% for the line flux ratios.…”
Section: Dust Grainssupporting
confidence: 93%
“…Two key types of models might explain the CLs and their properties: either photoionization by the central continuum source (e.g. Korista & Ferland 1989; Oliva et al 1994; Binette et al 1997; Ferguson et al 1997a; Nagao et al 2003; Mullaney et al 2009), or shock ionization or other processes directly or indirectly linked to the presence of radio jets (e.g. Tadhunter et al 1988; Viegas‐Aldrovandi & Contini 1989; Morse, Raymond & Wilson 1996; Axon et al 1998).…”
Section: Demystifying the Coronal‐line Region Of Active Galactic Numentioning
confidence: 99%
“…On one hand, authors have attempted to match CL strengths in samples of Seyfert galaxies, with an eye on the highest observed line ratios of CLs relative to low‐ionization lines (e.g. Erkens et al 1997; Komossa & Schulz 1997; Binette 1998; Rodríguez‐Ardila et al 2002; Nagao et al 2003; Rodrígue‐Ardila et al 2006). On the other hand, attention has focused on individual well‐studied Seyfert galaxies which have spatially resolved NLRs, and photoionization models have been presented which successfully reproduce the emission‐line ratios (with focus on low‐ionization lines, but including [Ne v ] and [Fe vii ]) of individual clouds.…”
Section: Demystifying the Coronal‐line Region Of Active Galactic Numentioning
confidence: 99%
“…This was so that the cloudy results were not affected by the depletion of iron due to condensation on to dust grains. Nagao et al (2003) have demonstrated for a large sample of AGNs that the observed FHIL ratios 7 cannot be reproduced in cloudy models that contain grains, but can be successfully reproduced with models not containing grains.…”
Section: Discussionmentioning
confidence: 99%